PENGARUH PENAMBAHAN KITOSAN DAN PLASTICIZER SORBITOL PADA PROSES PEMBUATAN PLASTIK BIODEGRADABLE BERBAHAN DASAR PATI KULIT PISANG TANDUK - Cengristitama, Cengristitama; Herdiansyah, Herdiansyah; Sari, Myra Wardati (UPPM Politeknik TEDC Bandung, 2023)
Biodegradable plastic is a type of plastic that will decompose in nature with the help of microorganisms, making it more environmentally friendly and an alternative solution to the problem of synthetic plastic waste made from petroleum. To obtain biodegradable plastic, starch can be added with a plasticizer called sorbitol, resulting in a more flexible and elastic plastic. The use of horned banana peel starch as the main material for making plastic has great potential because horned banana peels are still abundant waste in Indonesia and contain a significant amount of starch, around 29.60%. This research examines the use of horned banana peel starch as the main material for making biodegradable plastic. The aim of this research is to determine the effect of adding sorbitol and chitosan as plasticizers to horned banana peel starch-based plastic. The research used the melt intercalation method, with 16 trials, each using 10 grams of dried horned banana peel starch, and conducted three tests including thickness, water resistance, and plastic biodegradation. The composition of horned banana peel starch, chitosan, and sorbitol had an effect on the characteristics of biodegradable plastic. The best characteristics of biodegradable plastic were found in sample B1 (with a composition of starch : chitosan : sorbitol = 10 g: 2 g: 2,5 mL), which has a biodegradable plastic thickness of 0.23 mm, water resistance of 98%, and a complete biodegradation time in 7 days.